Estimate of projectile initial velocity as a solution of a two-point boundary value problem - Khaikov, Vadim L. (Vojnotehnički glasnik / Military Technical Courier, 2017)
The estimating of a projectile initial velocity is formulated as a two-point boundary value problem. To solve it, the data of a Doppler Radar or the results of solving the Cauchy problem can be used. The projectile initial velocity v0 estimation process is based on the numerical solution of a system of ordinary differential equations and the bisection method. The iterative calculating process is interrupted when a predetermined accuracy of a projectile initial velocity and a predetermined value of the width of velocity’s search interval is reached. In the article, the block diagram of the algorithm for the projectile initial velocity process is developed. The Mathcad program code for mathematical modeling and a computer simulation of the projectile initial velocity estimation process for a 57mm armor-piercing projectile of ZIS-2 anti-tank gun 1943 model is given.